RESISTANCE MECHANISM STUDIES IN SELECTED RICE GENOTYPES AGAINST BROWN PLANTHOPPER, NILAPARVATA LUGENS (STAL) - B , ANUSHA (The Journal of Research ANGRAU, 2026)
Twelve identified rice genotypes along with susceptible check (TN 1) and resistant check(PTB 33) were investigated for resistance against BPH during rabi 2021-22 at Regional AgriculturalResearch Station, Maruteru, Andhra Pradesh. Preference/non-preference mechanism wasassessed through honeydew excretion studies and tolerance was measured through number ofdays to wilt. Brown planthopper fed on these genotypes excreted significantly lower quantity ofhoneydew than the susceptible TN 1 (529.33 mm2). Among the genotypes, PTB 18 and HWR-21IR 71033-121-15-B recorded minimum honeydew excreted area of 91.00 mm2 and were equivalentwith the resistant check (78.67 mm2). The number of days taken by the genotypes to wilt rangedfrom 21.33 to 34.67 days. The susceptible check TN 1 and resistant check PTB 33 took 21.33and 34.67 days to wilt respectively. Among the genotypes, MTU 2837-31-1-1-1 took longer (32.33days) to wilt followed by PTB 18 which took 30.33 days.